The necromancer eaudiobook - Scott, Michael (The Secrets of the Immortal Nicholas Flamel, 2010)
Nicholas Flamel appeared in J.K. Rowling’s Harry Potter—but did you know he really lived? And his secrets aren't safe! Discover the truth in book four of the New York Times bestselling series the Secrets of the Immortal Nicholas Flamel.   The Belief: Sophie and Josh are the twins of prophecy. The Reality: Nicholas Flamel has been wrong before. Sophie and Josh Newman are finally home, but they're both more confused than ever about their futures.    Neither of them has mastered the elemental magics they'll need to protect themselves from the Dark Elders, they've lost Scatty, Macchiavelli is coming to unleash on their city the menagerie of monsters imprisoned in Alcatraz, and they're still being pursued by Dr. John Dee. And most disturbing of all is that now they must ask themselves, can they trust Nicholas Flamel?    Worse, can they trust anyone? “The Secrets of the Immortal Nicholas Flamel has everything you loved about Harry Potter , including magic, mystery, and a constant battle of good versus evil. ”— Bustle Read the whole series! The Alchemyst The Magician The Sorceress The Necromancer The Warlock The Enchantress